2020
DOI: 10.3389/fcell.2020.582380
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Gains of Aerobic Exercise in Patients With Ischemic Cerebrovascular Disorder: A Systematic Review and Meta-Analysis

Abstract: Background: Cognitive impairment has become an important problem in ischemic cerebrovascular disorder survivors as disease related deaths have been significantly reduced. Aerobic exercise, the most prevalent mode of physical activity, positively contributes to cognition in both healthy population and people with cognitive impairment. However, studies on its associations with cognitive gains in patients with ischemic cerebrovascular disease showed mixed findings.Objective: To explore the cognitive effects of ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 79 publications
(92 reference statements)
1
9
0
Order By: Relevance
“…It believed that gender might be an important factor affecting the effectiveness of aerobic exercise in improving executive function, and women can benefit a lot from aerobic exercise. [ 28 ] Similarly, in our study, all the trials included in the analysis were male dominated. Therefore, more large-scale studies are needed to determine the impact of aerobic exercise on executive function, and to determine whether gender and disease site affect the intervention effect.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It believed that gender might be an important factor affecting the effectiveness of aerobic exercise in improving executive function, and women can benefit a lot from aerobic exercise. [ 28 ] Similarly, in our study, all the trials included in the analysis were male dominated. Therefore, more large-scale studies are needed to determine the impact of aerobic exercise on executive function, and to determine whether gender and disease site affect the intervention effect.…”
Section: Discussionsupporting
confidence: 56%
“…Compared with similar studies, the effect size obtained in this study was significantly higher than that in Shu et al’s study (d = 0.13). [ 28 ] Shu et al focused on the effects of aerobic exercise on cognitive ability in survivors of ischemic cerebrovascular disease, but not all subjects were stroke patients. In contrast, the 11 articles included in this research only involved stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence 121 suggests that physical activity is an intervention with a protective role that may improve poststroke cognition. In addition, it is a low-cost strategy with a positive impact on motor function, quality of life, and cardiopulmonary condition.…”
Section: Cognitionmentioning
confidence: 99%
“… 9 However, these underlying mechanisms have been shown to exist only in animal models, and a number of studies that have examined these mechanisms have not yet shown that they are applicable to humans. Previous relevant studies have shown that distinctive types of exercise, such as aerobic exercise (AE) and resistance exercise (RE), might exert effects through some different molecular mechanisms and lead to various effect sizes (e.g., RE: standard mean difference (SMD) = 0.41−0.71; 10 , 11 , 12 AE: SMD = 0.13−0.58 12 , 13 ). Therefore, the type of exercise is an important factor that should be considered when clinical professionals prescribe exercise to prevent or slow cognitive decline.…”
Section: Introductionmentioning
confidence: 99%